Edukacja domowa – kilka uwag w kontekście dyskursu o edukacji demokratycznej - Helios, Joanna (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
The article presents home teaching in the context of the discourse on democratic education. The author discusses two problems: first, the role of home schooling in the context of compulsory schooling and the right to education; secondly, the legal aspects of home schooling.